Is testing the voice under sedation reliable in medialization thyroplasty?. (1st October 2016) - Oishi, Natsuki; Herrero, Ricard; Martin, Ana; Basterra, Jorge; Zapater, Enrique
Abstract : Objectives. Medialization thyroplasty is an accepted method for improving non-compensated unilateral vocal cord palsy. Most surgeons decide the depth of penetration of the prosthesis by monitoring the voice changes in the patient during the surgical procedure. General anesthesia with intubation is incompatible with this procedure. Sedation is recommended. In this study we want to objectivize and quantify the influence of sedation and position on voice in order to know if this anesthetic procedure is justified in medialization thyroplasties. Study design. A prospective study. Methods. This study involved 15 adult patients who underwent sedation. Voice recordings were performed in each patient in three different positions and conditions: the seated position without sedation, the supine position without sedation, and the supine position under the effects of sedation. The sedation drugs used were midazolam, fentanyl, and propofol. The level of sedation was monitored using the observational scale and the bispectral index. Results. The acoustic data obtained from sustained vowel sounds from patient recordings showed that sedation significantly affected the values of pitch. Compared to recordings from patients without sedation, pitch values in patients under sedation were significantly higher for jitter local and shimmer local recordings and significantly lower for pitch and harmonics-to-noise ratio. The supine position was shown not to influence on the voice. Conclusions. Sedation exerts an important influence on voice quality. General anesthesia could be an alternative, focusing our attention on monitoring the glottis with a fibrolaryngoscope during the surgical procedure. No sedation at all can also be an alternative.